Highly efficient, economic, and recyclable glutathione decorated magnetically separable nanocomposite for uranium(VI) adsorption from aqueous solution. (December 2020) - Sharma, M.; Chaudhary, K.; Kumari, M.; Yadav, P.; Sachdev, K.; Chandra Janu, V.; Gupta, R.
Abstract: A green and environment-friendly magnetically separable nanocomposite, glutathione@magnetite was fabricated sonochemically through the functionalization of Fe3 O4 by glutathione which was well characterized using Fourier-transform infrared spectroscopy, ultravoilet-visible spectroscopy, scanning electron microscope, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, thermogravimetric analysis, vibrating sample magnetometer, Brunauer-Emmett-Teller, and high-resolution transmission electron microscope. The parameters affecting adsorption including pH, temperature, contact time, initial adsorbate concentration, and adsorbent amount were optimized by batch experiments. The magnetic glutathione@magnetite was applied for the removal of uranium(VI) in water with maximum adsorption capacity found to be 333.33 mg/g in 120 min at a neutral pH at 25 °C showing high efficiency for U(VI) ions. Furthermore, adsorption results obtained from UV-vis spectroscopy were validated by inductively coupled plasma optical emission spectroscopy. The thermodynamic parameters, viz Gibbs free energy (ΔGº), standard enthalpy change (ΔHº), and standard entropy change (ΔSº) of the process were calculated using the Langmuir constants. The pseudo-second-order kinetics model is seen to be applicable for describing the uptake process using a kinetics test. Moreover, desorption studies reveals that glutathione@magnetite can be used repeatedly, and removal efficiency shows only a small decrease after six cycles. Thus, glutathione@magnetite acts as a potential adsorbent for the removal of U(VI) from the water with great adsorption performance. Graphical abstract: Image 1 Highlights: A novel magnetically separable nanocomposite i.e., glutathione@magnetite was successfully synthesized by chemical route. Glutathione@magnetite exhibits excellent adsorption toward U(VI) at a neutral pH = 7. Maximum adsorption capacity attained from Langmuir isotherm was 333.33 mg/g. Adsorption and desorption studies were conducted with almost 90% U(VI) adsorption even after 6 cycles.